2024
DOI: 10.32859/era.28.2.1-21
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Indigenous Ethnobotanical Knowledge of Medicinal and Aromatic Plants from Kashmir Himalayan Region

Syed Waseem Gillani,
Mushtaq Ahmad,
Muhammad Zafar
et al.

Abstract: Background: Documenting traditional knowledge of medicinal plants has enabled researchers to obtain a good understanding of the consumption patterns of plants for basic healthcare purposes. This study highlighted the ethnobotanical significance of medicinal and aromatic plants in the biodiversity hotspot landscape of the western Himalayan region of Kashmir.Methods: Extensive field visits were made to collect traditional ethnobotanical knowledge from the study area through group discussions in the local languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Curcuminoids are useful for a variety of applications, including spices, coloring pigments, additives, and medicines (15). As the pharmaceutical industry continues to expand, there is an increasing need for plant-based raw materials to extract a wide array of bioactive compounds (16)(17)(18)(19). Preserving key components like phenolic and bioactive compounds such as curcuminoids from Curcuma spp.…”
Section: Introductionmentioning
confidence: 99%
“…Curcuminoids are useful for a variety of applications, including spices, coloring pigments, additives, and medicines (15). As the pharmaceutical industry continues to expand, there is an increasing need for plant-based raw materials to extract a wide array of bioactive compounds (16)(17)(18)(19). Preserving key components like phenolic and bioactive compounds such as curcuminoids from Curcuma spp.…”
Section: Introductionmentioning
confidence: 99%
“…In remote parts of Pakistan, knowledge of traditional medicine helps researchers to explore new medicinal plants with valuable medicinal properties. Ethnobotanical studies on medicinal plants have been carried out mostly across different parts of Northern Pakistan, i.e., Khyber Pakhtunkhwa, Gilgit Baltistan, Azad and Jammu Kashmir (Gillani et al 2024, Mirzaman et al 2023. The Punjab province has diverse sorts of climatic regions and has the potential to host a great diversity of plants (Jamil et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the imperative of sustainable resource management and the urgent need to mitigate environmental degradation underscores the need to document, understand, and harness the potential of these plants. Several previous studies have shown a significant lack of intergenerational transfer of traditional knowledge, resulting in the loss of an immense volume of invaluable data regarding native plant species due to the limited accessibility of written documents and records (Mirzaman et al 2023;Manzoor et al 2023;Gillani et al 2024). In addition, reports from the same region suggest a significant loss of traditional knowledge, which could hinder the transmission of locally communicated information regarding various plant-based treatment approaches (Shinwari et al 2011).…”
Section: Introductionmentioning
confidence: 99%